2007
DOI: 10.1080/07315724.2007.10719586
|View full text |Cite
|
Sign up to set email alerts
|

Poor Nutrient Intake and High Obese Rate in an Urban African American Population with Hypertension

Abstract: In order to reduce the incidence of obesity and hypertension in this minority population, dietary intervention should begin at adolescence or even earlier. DASH diet would be beneficial for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In a study conducted by Hart et al (2006), fat summary scores among males indicated higher fat intake (n = 329, fat score = 2.57, SD = .44, p < .001) compared to females (n = 2,030, fat score = 2.44, SD = .41). Similarly, Jen et al (2007) found that males' total fat (64.5 grams) and saturated fat (20.3 grams) intake was significantly higher than females' total fat (49.6 grams) and saturated fat (16 grams) (p < .001) intake.…”
Section: Gender and Dfimentioning
confidence: 84%
See 4 more Smart Citations
“…In a study conducted by Hart et al (2006), fat summary scores among males indicated higher fat intake (n = 329, fat score = 2.57, SD = .44, p < .001) compared to females (n = 2,030, fat score = 2.44, SD = .41). Similarly, Jen et al (2007) found that males' total fat (64.5 grams) and saturated fat (20.3 grams) intake was significantly higher than females' total fat (49.6 grams) and saturated fat (16 grams) (p < .001) intake.…”
Section: Gender and Dfimentioning
confidence: 84%
“…(2007), Hart et al (2006), andJen et al (2007) found no significant relationship between income and dietary fat intake. When Hart et al (2006) adjusted for age, there was a significant relationship with fat intake (p = .001); however when they included education in the model the relationship was no longer statistically significant (p = .18).…”
Section: Income Adequacy and Dfimentioning
confidence: 95%
See 3 more Smart Citations